Landfill management and efficacy of anaerobic reactors in the treatment of landfill leachate - Imran, Ahmad; Aida Batrisyia, Jasni; Norhayati, Abdullah; Krishnan, Santhana; Iwamoto, Koji; Chelliapan, Shreeshivadasan; Yuzir, Muhamad Ali Muhammad; Mohd, Nasrullah (Elsevier, 2022)
Increasing thrust on technological advancement around the globe has led to a drastic increase in the consumption of various products or raw materials consequently leading to an enormous amount of solid waste generation. In the developing countries mainly sanitary landfills are opted for the disposal of solid waste because of the economic advantage but it results in the generation of highly polluted complex and recalcitrant leachate. Leachate is generated due to the percolation of rainwater and the decomposition of the waste. The leachate contains dissolved organic compounds, heavy metals, ammonia, xenobiotic(compounds phenols) and pesticides, and inorganic salts. Therefore it is extremely recommended that leachate should be treated before disposal into the environment as it can pollute the soil, surface, and groundwater bodies. the quantity of leachate generated depends upon the amount of rainfall, surface runoff, and the rate of infiltration while the quality of landfill digit depends upon several factors, that is, composition of the solid waste coming to the landfill, the age of the landfill, and the climatic conditions. The biodegradability of landfill digits is a crucial factor and it is inversely related to the age of the landfill, transforming the organic fraction present in the solid waste to the recalcitrant nonbiodegradable compounds. Therefore landfill leachate should be treated at an early stage to maximize the production of biogas and the efficiency of the removal of pollutants. Biological treatment is generally adopted for the treatment of landfill leachate because of its reliability, ease of operation, and cost-effectiveness they can be classified into Aerobic and anaerobic processes where anaerobic processes are having an upper hand because of the following advantages: Less sludge production; cost and energy-intensive; and the production of biogas which can be used as a source of renewable energy leading to the sustainability of the environment. Therefore various anaerobic reactors are used in the treatment of landfill leachate such as upflow anaerobic sludge blanket reactor, anaerobic baffled reactor, Anammox reactor, etc. Nevertheless, due to the complex and varying characteristics of landfill leachate sometimes conventional technologies cannot efficiently and effectively treat the landfill leachate compelling the requirement of physical and chemical treatments being integrated with the biological to achieve the desired/acceptable standards of the effluent. This chapter will provide an insight into the landfill management, characteristics, and deleterious effects of landfill leachate, and different anaerobic reactors involved in the treatment of landfill leachate.